Anatomic Outcomes of Robotic Assisted Supracervical Hysterectomy and Concurrent Sacrocolpopexy at a Tertiary Care Institution at Initial Adaptation of the Procedure. Issue 1 (January 2016) - Prendergast, Emily; Silver, Hayley; Johnson, Lisa Labin; Simon, Melissa; Feinglass, Joseph; Kielb, Stephanie; Hairston, John; Lewicky-Gaupp, Christina
Abstract : Objective: The aim of the study was to review anatomic and surgical outcomes of robotic-assisted supracervical hysterectomy (RASCH) with concurrent sacrocolpopexy in the treatment of primary pelvic organ prolapse (POP) on initial adaption of this procedure. Study Design: A retrospective chart review of patients undergoing RASCH with concurrent sacrocolpopexy between 2009 and 2012 was performed at a tertiary care academic institution, after initial adaption of this procedure. The primary outcome was change in vaginal support (assessed with the pelvic organ prolapse quantification [POP-Q]) at 3 months and 1 year postoperatively. Secondary measures assessed included estimated blood loss, operative times, hospital length of stay, and operative complications. Results: Forty patients (N = 40) underwent RASCH with concurrent sacrocolpopexy. Twenty-six patients (65%) had preoperative stage II POP, and 35% had stage III POP. Three months after undergoing the procedure, 55% had achieved stage 0 POP. An additional 35% were categorized as stage I POP. At 1 year, 72.7% were stage I POP or lower. The mean (SD) operating time was 275 (82.3) minutes. Estimated blood loss and mean (SD) length of hospital stay were 163 (114.9) mL and 1.3 (0.8) days, respectively. There were no intensive care unit admissions. The most common postoperative complication was immediate urinary retention in 10% of patients; all cases resolved with time-limited intermittent self-catheterization. Conclusions: Even with initial adaptation of the procedure, RASCH with concurrent sacrocolpopexy for the repair of primary POP is effective in restoring anatomic support in the short term. Operative complications are minimal. Abstract : Even on initial adaptation of the procedure, robotic-assisted supracervical hysterectomy with concurrent sacrocolpopexy is an effective means of restoring anatomic support in women with primary pelvic organ prolapse repair in the short term.